Venetoclax plus hypomethylating agents versus intensive chemotherapy for hematological relapse of myeloid malignancies after allo-HSCT - Chen, Zhangjie; Zhen, Sisi; Zhang, Tingting; Shen, Yuyan; Pang, Aiming; Yang, Donglin; Zhang, Rongli; Ma, Qiaoling; He, Yi; Wei, Jialin; Zhai, Weihua; Chen, Xin; et al. (Frontiers in Oncology, 2023)
Since allogeneic stem cell transplantation (allo-HSCT) represents one of the curative treatments for acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS), hematologic relapse after allo-HSCT remained a critical issue for patients’ survival. We retrospectively compared patients who received VEN+HMA (n=20) or IC regimen (n=38) for hematological relapse of myeloid malignancies after allo-HSCT. HMA selection included decitabine (n=2) and azacitidine (n=18). Donor lymphocyte infusion was administered in 18 and 38 patients in VEN+HMA and IC groups, respectively. Median age of all patients was 39 (16-64) years old. Overall response rate, including CR, CRi and PR, and CR/CRi rate was 60.0% and 50.0% in VEN+HMA group versus 68.4% (P=0.521) and 63.2% (P=0.334) in IC group, respectively. Rate of relapse after response was 60.0% (VEN+HMA) and 41.7% (IC) (P=0.708). Median OS was 193.0 (95%CI 118.4-267.6) days for VEN+HMA group versus 205.0 (95%CI 0-410.5) days for IC group (P=0.617). Lung infection (15.0% versus 50.0%, P=0.009), thrombocytopenia (75.0% versus 97.4%, P=0.027) and acute GvHD (50.0% versus 10.0%, P=0.002) occurred significantly more frequently in IC group. In conclusion, VEN+HMA is not inferior to IC regimen in achieving response and prolonging survival, also with lower incidences of adverse events and acute GvHD.